Simultaneous determination of endocrine disrupting compounds in estuarine water, sediment and mariculture fishes through extraction coupled with liquid chromatography-mass spectrometry and human health risk management - Ismail, Nur Afifah Hanun (2020)
Endocrine disrupting compounds ( EDCs) are emerging pollutants causing global concern because they can disrupt the endocrine system in aquatic organisms, mammals, and humans. Because EDCs have been introduced into aquatic ecosystems, the exposure of humans and animals that depend on aquatic foods, especially fishes, should be seriously considered. These pollutants have been released into the environment through many sources, e.g., wastewater treatment plants, terrestrial run-off (industrial activities,pharmaceuticals, and household waste), and precipitation. The use of hormone, pharmaceuticals, pesticides, and fertilizers for maintaining and increasing fish health and growth also contributes to EDC pollution in the water body. Pulau Kukup, Johor, Malaysia is one of the biggest mariculture areas that is actively involved in marine fish export to other countries. As aquaculture production through mariculture activities in Malaysia support food production, the concentration and distribution of EDCs in aquatic ecosystem need to bemonitored to secure the food safety. The aim of this study i s to optimize a suitable and reliable method to be applied on environmental samples (estuarine water and sediment) and biota sample (mariculture fish) and for the determination of EDCs pollutant in Pulau Kukup, Johor. Besides, this study also presented the human health risk assessment associated with the consumption of fish from Pulau Kukup, Johor, Malaysia. The method displays a high extraction recovery for estuarine water sample, sediment, and mariculture fish in current study, ranging from 92.02% to 132.32 %, 50.39 to 129.10%, and 52.94- 125.95% respectively. The highest concentration EDCs detected in estuarine water sample is diclofenac (< 0.47-79.72 ng/L) followed by E2 (< 5.28-31.11 ng/L) and EE2 (< 0.30-7.69 ng/L). In sediment, bisphenol A (0.072-0.389 ng/g dry weight) was observed as the highest concentration, followed by diethylstilbestrol (< 0.208-0.331 ng/g dry weight) and propranolol (< 0.250-0.275 ng/g dry weight). Meanwhile in fish, the highest concentration of EDCs were detected in muscle, liver, and reproductive organ is dexamethasone (15.84 ng/g, dried muscle), dexamethasone (43.56 ng/g), andE2 (44.85 ng/g) respectively. Based on human health risk calculation in this study, five targeted EDCs (progesterone, bisphenol A, primidone, sulfamethoxazole, and diclofenac) shown no potential health risk (HQ < 1) with the consumption of fish from this mariculture site. This current study can be a baseline assessment for EDCs pollution profile and distribution in the coastal ecosystem from mariculture site throughout the world especially in Malaysia. The data obtained should be relevance to decision-making legislation and policy ratification for food safety to improve the quality of protein based food and reduce environmental pollution. Owing to the significant concentration of targeted EDCs detected in estuarine water sample, sediment, and mariculture fish, the need to further monitoring in future are required. Although the concentration of targeted compounds obtained are low but their effects may appear in the long term period and this situation alarms not only the environment health but also cause the potential risk to human.